(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical and paraclinical characteristics of patent ductus arteriosus in preterm infants and evaluate the outcomes of Ibuprofen in closing the ductus arteriosus in preterm infants at Nghe An Obstetrics and Pediatrics Hospital. Subjects and Methods: A prospective descriptive study combined with a retrospective review was conducted among 88 neonates who were hospitalized in the Neonatal Intensive Care Unit at Nghe An Obstetrics and Pediatrics Hospital from January 2023 to September 2024. Results: The rate of preterm infants with patent ductus arteriosus requiring invasive mechanical ventilation was 88.6%. The majority of patients required intravenous fluids for nutrition. A total of 79.5% of infants achieved successful ductal closure, with 18.1% of them undergoing a second closure after receiving Ibuprofen. Conclusion: The rate of preterm infants with patent ductus arteriosus requiring invasive mechanical ventilation before treatment was very high at 88.6%. After administering Ibuprofen, the success rate for ductus arteriosus closure was quite high at 79.5%, including 18.1% who needed a second attempt for closure.